Amino acid supplements and recovery from high-intensity resistance training - Sharp, C. P. M.; Pearson, D. R. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to investigate whether short-term amino acid supplementation could maintain a short-term net anabolic hormonal profile and decrease muscle cell damage during a period of high-intensity resistance training (overreaching), thereby enhancing recovery and decreasing the risk of injury and illness. Eight previously resistance trained males were randomly assigned to either a high branched chain amino acids (BCAA) or placebo group. Subjects consumed the supplement for 3 weeks before commencing a fourth week of supplementation with concomitant high-intensity total-body resistance training (overreaching) (3 × 6-8 repetitions maximum, 8 exercises). Blood was drawn prior to and after supplementation, then again after 2 and 4 days of training. Serum was analyzed for testosterone, cortisol, and creatine kinase. Serum testosterone levels were significantly higher (p < 0.001), and cortisol and creatine kinase levels were significantly lower (p < 0.001, and p = 0.004, respectively) in the BCAA group during and following resistance training. These findings suggest that short-term amino acid supplementation, which is high in BCAA, may produce a net anabolic hormonal profile while attenuating training-induced increases in muscle tissue damage. Athletes' nutrient intake, which periodically increases amino acid intake to reflect the increased need for recovery during periods of overreaching, may increase subsequent competitive performance while decreasing the risk of injury or illness.